An Approach to Chemical Reaction Engineering and Process Intensification for the Lean Aqueous Hydroformylation Using a Jet Loop Reactor. Issue 5 (16th January 2019) - Esteban, Jesús; Warmeling, Helge; Vorholt, Andreas J.
Abstract: The biphasic hydroformylation of 1‐octene using a lean aqueous phase as solvent phase for catalyst recycling is discussed here. The gas‐liquid‐liquid reaction was homogeneously catalyzed by industrial standard catalytic system with [Rh(cod)Cl]2 as precursor and TPPTS as ligand. This work summarizes investigations addressing different aspects of the reaction, where a procedural approach was followed to gain understanding of its nature, kinetics and interphase reactivity. Finally, the application of the jet loop reactor is analyzed as a means to intensify the reaction. Abstract : The hydroformylation of long chain olefins is a paradigmatic example of a gas‐liquid‐liquid reaction where recycling of costly catalysts is of paramount importance. A procedural approach is followed to study the kinetics of the reaction, interfacial reactivity and the application of a jet loop reactor to intensify the contact among the phases.